UTILIZING THE MIT APP INVENTOR TOOLS AS A LEARNING MEDIA INFORMATION TO CREATE ANDROID-BASED APPLICATIONS - Saputra, Ricco Herdiyan; Waziana, Winia (Universitas Islam Negeri Raden Intan Lampung, 2023)
The rapid development of digital technology currently provides many benefits to humans. For example, the development of software or various technological tools that support activities and provide convenience in human life. With the development of the times, software is increasingly sophisticated in various fields, one of which is the field of education. In supporting the learning process, the education sector must follow and adapt existing technology. As is the case with learning media that currently uses an Android-based operating system. Therefore, it is very necessary to educate and teach how to build applications using the operating system. Based on the current problems, the authors provide an educational solution with